Operational Evaluation Of Kmp. Siginjai Crossing Jepara – Karimunjawa In Central Java Province - Purboyo Purboyo; Dahlia Dewi A; Dwi Tuti Waliyani (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2022)
Jepara Ferry Port is a port that connects Java to Karimunjawa islands. This port is busy being used to transport vehicles, passengers, and basic food items for crossings, one of the ships used is KMP. Siginjai. The purpose of this study was to determine the operational load factor of KMP. Siginjai in the Jepara - Karimunjawa crossing and to arrange ship schedules based on the required frequency. The method used in this study is a survey method which is divided into two data collection methods, those are primary data and secondary data, primary data in the form of observation and secondary data in the form of institutional methods. In analyzing the data, several types of analysis were used, those are load factor analysis, passenger growth analysis, ship scheduling analysis and ship operational time analysis. Based on data analysis, it is known that the number of ships serving the Jepara – Karimunjawa route is not in accordance with the needs of service users. Based on the analysis of ship needs and facilities to serve the number of existing ships. The number of trips and the frequency of ship departures are currently not in accordance with the needs of service users. this is because the trip on the Jepara - Karimunjawa route is only 1 (one) trip / day which causes service users not to be transported to the ship and have to wait for the next departure. because the ship has excess load capacity.